Електрохімічні та електрохемілюмшесцентні дослідження нанорозмірних частинок типу CdTe у водних розчинах - Галайченко, О. М.; Білаш, О. М. (ХНУРЭ, 2008)
Semiconductor spherical quantum dots (QD) are the new material for different kinds of investigations and application because of their unique electronic and optic behavior. In this work electrochemical and electrochemiluminescent properties of CdTe quantum dots were investigated with the purpose of using them as detection elements of sensor instrument for early definition of active tuberculosis process markers.
Keywords: дослідження нанорозмірних частинок; водний розчин